A study of morphological evolution of silicon microstructure based on phase field model. (18th November 2017) - Zhang, Linan; Zheng, Wei; Lee, Jungchul; Wu, Liqun; Kim, Dongchoul
ABSTRACT: A three dimensional model for a nano/microfabrications of silicon on nothing (SON) structure based on phase field model has been presented. The temperature induces morphological evolution of silicon substrate has been introduced and suggested as a great possibility for the evolution dynamics. Phase field model is employed to present the morphological evolution of silicon. The numerical simulations represent an efficient verification on the experimental work. The performed work could present a detailed process of the cavity formed in the silicon substrate under high temperature. The mechanism for making the cavity in the silicon substrate is the shape changes, which is caused by surface diffusion and driven by the minimization of their surface energy. The aim of this paper is providing a reliable fabrication process of silicon substrate in high temperature, and control the fabrication process when the annealing is performed. The performed simulation results are well consistent with the experimental works.